Da’wah Bil Hal and Muslim Women’s Religious Humanist Ideology in Indonesian Film - Rizka Gusti Anggraini; Rubino Rubino; Irma Yusriani Simamora (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
This study aims to find out the overview of da'wah bil hal as an approach for proselytizing through actual actions or the role model from attitudes and behaviours represented in the religious film entitled